Inverse problem for a fourth-order parabolic equation considering the additional high-order derivative in the initial condition.: Inverse problem for a fourth-order parabolic equation considering the additional high-order derivative in the initial condition. - Ubaydulloev, A. N. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Introduction We consider an inverse problem in this article. Actually, when high-order derivatives with respect to t, exceeding the order of the equation are specified in the initial conditions. A.N. Tikhonov was the first to study the problem with a high-order derivative on part of the domain boundary. A problem for the homogeneous heat equation with the following conditions was studied in [1]